1995
DOI: 10.1186/1297-9686-27-4-365
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of growth curves in poultry

Abstract: This paper compares the growth patterns of chickens, turkeys, ducks and geese. The growth curves and their parameters were estimated by the Richards function. In this work, weight data of females of current sire lines (62 chickens, 47 ducks and 42 geese) and commercial medium-type hybrids (27 turkeys) were used. Birds were fed ad libitum and weighed at 7 or 14 d intervals up to 18-28 weeks of age. The accuracy of the curve fit was high in all species (R 2 = 0.9840 to 0.9994). The ratios y + /A (weight at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…At the age of 26 weeks, chicken growth is in the stationary phase. Thus, in this phase, chicken has reached the maximum growth (Knízetová et al, 1995). Results of our study showed no significant effect between the g.2248G>A GH polymorphism and chicken carcass components.…”
Section: Discussionmentioning
confidence: 53%
“…At the age of 26 weeks, chicken growth is in the stationary phase. Thus, in this phase, chicken has reached the maximum growth (Knízetová et al, 1995). Results of our study showed no significant effect between the g.2248G>A GH polymorphism and chicken carcass components.…”
Section: Discussionmentioning
confidence: 53%
“…Reports describing the growth curve with a mathematical function suggest that the inflection point of the growth curve, that is, the end of the acceleration phase and the onset of the retardation phase, varies in the meat-type chickens between 6 and 9 weeks of age depending on selection traits used for their formation (Leclercq et al, 1989;Knížetová et al, 1991Knížetová et al, , 1995Mignon-Grasteau et al, 2000). In contrast, in the meat-type quail this was usually observed between 2 and 3 weeks of age (Marks, 1978;Anthony et al, 1991;Hyánková et al, 1998Hyánková et al, , 2001Hyánková et al, , 2002.…”
Section: Discussionmentioning
confidence: 81%
“…This ratio estimates the maturation rate of the curve (i.e. the relative rate at which M is reached) (Knízetová, 1995 Anthony et al (1996) and Aggrey et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…the relative rate at which asymptotic body weight is reached) (Knízetová, 1995). In HW line, the low value of β expressed lower maturation rate, compared to LW and C lines (P<0.05).…”
Section: The C Linementioning
confidence: 99%